India-Bangladesh Relations: Past, Present and Future - Rahman, Muhammad Mahmudur; Islam, Md. Shofiqul (International Journal of Humanities, Education, and Social Sciences, 2025)
India’s contribution in the liberation war of Bangladesh was outstanding. Friendship relation exists between the two countries since the liberation war of Bangladesh. As a large neighboring country, Bangladesh has maintained good relationship with India since birth. In this age of globalization, no country can meet its demand alone. Bangladesh also cannot meet alone. Bangladesh is dependent on other countries of the world for many things starting from daily necessities. Overall, Bangladesh is more dependent on its neighboring country India. Again, India is also dependent on neighboring Bangladesh in many ways. It is through this dependence that relationships are built. Since Bangladesh and India are both bordering countries, they have developed better relations than other countries in security, military, and other matters. Historically, there are many other reasons for the friendly relations between Bangladesh and India. Moreover, Bangladesh and India being members of SAARC and BIMSTEC have developed a special friendship between the two countries. India is considered as an eternal friend due to its contribution to the independence war of Bangladesh. There have been many ups and downs in the relations between India and Bangladesh since the pre-independence period. There have been discussions and criticisms on various issues between the two countries. Various initiatives have been taken to sweeten the relationship. This paper discusses the past history of the relationship between Bangladesh and India, the current situation of the relationship, and how the relationship will be stood in the future.